Strategi LAZISNU Jawa Barat dalam Mewujudkan Masyarakat Sadar Zakat - Jalaluddin Jalaluddin (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
The NU West Java Amil Zakat Infaq and Shadaqah Institute is an official zakat amil institution under the auspices of the West Java NU Regional Management with a work focus on empowering zakat, infaq and alms collected from the nahdiyin congregation, donors, corporates and the community in general. As an institution that has a very large congregation and jam'iyah base, LAZISNU West Java must take a role in encouraging people to have awareness in paying their zakat. Therefore, LAZISNU West Java needs an effective strategy in maximizing the potential of zakat. Thus, LAZISNU West Java must have an organizational institutional mission in developing zakat management, this of course will not achieve efforts to develop zakat management if all the potential that exists in developing zakat management will not be achieved. The method used is a qualitative descriptive approach. The results of this research, West Java LAZISNU creates a zakat aware society, of course assisted by LAZISNU in the Branches as well as West Java LAZISNU itself including (1) Internal Platform, (2) External Platform, (3) Collection of Zakat Infaq and Sadaqah within the Internal Nahdlatul Ulama Regional Management ( PWNU) West Java, (4) LAZISNU West Java provides a service office to collect Zakat, Infaq and Shadaqah funds, (5) Optimizing the NU Coin movement, (6) Advice on giving zakat, infaq and shaqadah from Nahdlatul Ulama figures at each lecture, tabligh akbar, regular recitations and any momentum.